2005
DOI: 10.1007/s00037-004-0186-2
|View full text |Cite
|
Sign up to set email alerts
|

Valiant?s model and the cost of computing integers

Abstract: Abstract. Let τ (n) be the minimum number of arithmetic operations required to build the integer n ∈ N from the constants 1 and 2. A sequence x n is said to be "easy to compute" if there exists a polynomial p such that τ (x n ) ≤ p(log n) for all n ≥ 1. It is natural to conjecture that sequences such as 2 n ln 2 or n! are not easy to compute. In this paper we show that a proof of this conjecture for the first sequence would imply a superpolynomial lower bound for the arithmetic circuit size of the permanent po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 16 publications
0
25
0
2
Order By: Relevance
“…The following result answers in the affirmative some questions posed by Koiran (2004). From the very general proof technique, it becomes obvious that this result actually holds for a large class of integer sequences, so the choice of the sequences below is for illustration and just motivated by Koiran's question.…”
Section: Connecting Valiant's Model To Integers and Univariate Polynomentioning
confidence: 64%
See 3 more Smart Citations
“…The following result answers in the affirmative some questions posed by Koiran (2004). From the very general proof technique, it becomes obvious that this result actually holds for a large class of integer sequences, so the choice of the sequences below is for illustration and just motivated by Koiran's question.…”
Section: Connecting Valiant's Model To Integers and Univariate Polynomentioning
confidence: 64%
“…Koiran (2004) proved the following weaker version of the statement regarding the factorials: if (n!) is hard to compute, then VP 0 = VNP 0 or P = PSPACE.…”
Section: The Sequence Of Taylor Approximationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, as explained below the study of VΠP 0 leads to meaningful results about the complexity of decision problems. This paper is therefore in the same spirit as [9], where it is shown that certain sequences of integers become easy to compute if certain classes of polynomial families coincide.…”
Section: Introductionmentioning
confidence: 97%